Application of protein or protein hydrolysates to improve postexercise recovery - van Loon, L. J. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
Protein, protein hydrolysates, and amino acids have become popular ingredients in sports nutrition. The use of protein, protein hydrolysates, and amino acid mixtures has multiple applications when aiming to improve postexercise recovery. After exhaustive endurance-type exercise, muscle glycogen repletion is the most important factor determining the time needed to recover. Coingestion of relatively small amounts of protein and/or amino acids with carbohydrate can be used to augment postprandial insulin secretion and accelerate muscle glycogen synthesis rates. Furthermore, it has been well established that ingesting protein, protein hydrolysates, and amino acid can stimulate protein synthesis and inhibit protein breakdown and, as such, improve net muscle protein balance after resistance- or endurance-type exercise. The latter has been suggested to lead to a more effective adaptive response to each successive exercise bout. To augment net muscle protein accretion, athletes involved in resistance-type exercise generally ingest both protein and carbohydrate during postexercise recovery. However, carbohydrate ingestion after resistance-type exercise does not seem to be warranted to further stimulate muscle protein synthesis or improve whole-body protein balance when ample protein has already been ingested. Because resistance-type exercise is also associated with a substantial reduction in muscle glycogen content, it would be preferred to coingest some carbohydrate when aiming to accelerate glycogen repletion. More research is warranted to assess the impact of ingesting different proteins, protein hydrolysates, and/or amino acids on muscle protein accretion after exercise.